Intracarotid Transplantation of Skin-Derived Precursor Schwann Cells Promotes Functional Recovery After Acute Ischemic Stroke in Rats - Liang, Jingjing; Cui, Ronghui; Wang, Jinglei; Shen, Jiabing; Chen, Ying; Cao, Maosheng; Ke, Kaifu (Frontiers in Neurology, 2021)
Purpose: Skin-derived Precursor Schwann cells (SKP-SCs) have been reported to provide neuroprotection for the injured and dysmyelinated nervous system. However, little is known about SKP-SCs on acute ischemic stroke (AIS). We aimed to explore the efficacy and the potential mechanism of action of SKP-SCs on AIS in a rat ischemic stroke model. Methods: Adult male Sprague–Dawley rats were subjected to a middle cerebral artery occlusion (MCAO) (1.5h) on Day 0 and subsequently received an intracarotid injection of 2×106 green fluorescent protein (GFP) -labeled SKP-SCs or phosphate buffered saline (PBS) during reperfusion. Neurological function was assessed by behavioral tests on days 1, 4, 7, 14, and 28. In a satellite cohort, rat brains were harvested and infarct volume was measured with 2,3,5-triphenyltetrazolium chloride (TTC) staining on days 1 and 7, and migration and survival of SKP-SCs in the brain were traced by monitoring green fluorescence on 6h, 12h, days 1, 4, 7, 14, and 28. Histopathology and immunofluorescence staining were used to analyze the morphology, survival and apoptosis of neurons. Additionally, in an in vitro SKP-SC co-culture model using fetal rat primary cortical neurons, Western blot was used to detect the expression of apoptosis indicators (activated caspase-3, Bax, and Bcl-2) and TUNEL-positive cells were counted. Results: Intracarotid transplantation of SKP-SCs effectively migrated to the periinfarct area and survived for at least 4 weeks. SKP-SCs transplantation inhibited neuronal apoptosis, reduced infarct volume, and improved neurological recovery in MCAO rats. Moreover, in vitro data showed that SKP-SCs treatment can inhibit OGD/R-induced neuronal apoptosis and promote neuron survival in the cultured primary cortical neurons. Conclusions: Our data suggest that intracarotid transplantation of SKP-SCs promotes functional recovery in the rat AIS model. SKP-SCs have the potential to be further developed as a novel therapy to treat ischemic stroke in humans.